var gene transcription and PfEMP1 expression in the rosetting and cytoadhesive Plasmodium falciparum clone FCR3S1.2 - Albrecht, Letusa (BioMed Central, 2011)
BACKGROUND: The pathogenicity of Plasmodium falciparum is in part due to the ability of the parasitized red blood cell (pRBC) to adhere to intra-vascular host cell receptors and serum-proteins. Binding of the pRBC is mediated by Plasmodium falciparum erythrocyte membrane protein 1 (PfEMP1), a large multi-variant molecule encoded by a family of ≈60 var genes. METHODS: The study of var gene transcription in the parasite clone FCR3S1.2 was performed by semi-quantitative PCR and quantitative PCR (qPCR). The expression of the major PfEMP1 in FCR3S1.2 pRBC was analysed with polyclonal sera in rosette disruption assays and immunofluorecence. RESULTS: Transcripts from var1 (FCR3S1.2(var)(1); IT4var21) and other var genes were detected by semi-quantitative PCR but results from qPCR showed that one var gene transcript dominated over the others (FCR3S1.2(var)(2); IT4var60). Antibodies raised in rats to the recombinant NTS-DBL1α of var2 produced in E. coli completely and dose-dependently disrupted rosettes (≈95% at a dilution of 1/5). The sera reacted with the Maurer's clefts in trophozoite stages (IFA) and to the infected erythrocyte surface (FACS) indicating that FCR3S1.2(var2 )encodes the dominant PfEMP1 expressed in this parasite. CONCLUSION: The major transcript in the rosetting model parasite FCR3S1.2 is FCR3S1.2(var)(2 )(IT4var60). The results suggest that this gene encodes the PfEMP1-species responsible for the rosetting phenotype of this parasite. The activity of previously raised antibodies to the NTS-DBL1α of FCR3S1.2(var)(1 )is likely due to cross-reactivity with NTS-DBL1α of the var2 encoded PfEMP1.